Juan Filhiol papers - Filhiol, Juan, 1740-1821.
Correspondence, orders, reports, petitions, land grant (Hot Springs, Ark.) with manuscript map, and other documents relating to Filhiol's service (1783-1800) as commandant of Ouachita, a region in the province of Louisiana, of which there is a description (1786) in French. Includes instructions (1783) of Estevan Miro to Filhiol, posthumous papers relating to the land claims of Filhiol's descendants.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts and photocopies.
Army officer.
Collection material in French, with English translations in part.
Keywords: Land grants -- Arkansas -- Hot Springs; Arkansas -- Maps; Louisiana -- History -- To 1803.; France -- Colonies; Army officers